Adult Degenerative Scoliosis - Alexandre Fogaça Cristante; Ricardo Teixeira e Silva; Guilherme Henrique Ricardo da Costa; Raphael Martus Marcon (Revista Brasileira de Ortopedia, 2021)
Abstract Populational aging increases the incidence of musculoskeletal degenerative processes, such as adult scoliosis (AS). Adult scoliosis is defined as a spinal deformity in the coronal plane with a Cobb angle > 10º. Adult scoliosis may be iatrogenic or result from a degenerative process (scoliosis de novo) or a pre-existing scoliosis. Adult scoliosis is a potentially limiting condition that affects a heterogeneous group of patients. Clinical treatment proved to be ineffective and surgery is often indicated. The present paper reviews AS pathophysiology, clinical presentation and diagnosis, in addition to surgical indications and the main techniques currently used.